A new species of Cycreon d’Orchymont, 1919 from Singapore (Coleoptera: Hydrophilidae: Megasternini) - Shatrovskiy, Alexander (Zootaxa, 2017)
The monotypic genus Cycreon Orchymont, 1919 was established for the species Cycreon sculpturatus Orchymont, 1919, based on a single female specimen from Palembang, Sumatra (Orchymont 1919). At some later point, d’Orchymont studied a specimen from Singapore and labelled it with a note indicating it may be either a male of C. sculpturatus or a new species (Fig. 27). Examination of the holotype of C. sculpturatus revealed the Singapore specimen does indeed represent a new species. It was additionally labeled by d’Orchymont: “Cycreon emarginatus n. sp. voir cependantsi ce n’esl pas le ♂ de sculpturatus” [Cycreon emarginatus n. sp. however, whether is it not the male of C. sculpturatus] but it has never been described.